IOT Based Synchronous Smart Traffic Monitoring System with Data Sharing Capability - Kachhavey, Hemlata; Khan, Mubeen Ahmed (International Journal of Computer Sciences and Engineering, 2020)
In recent years’ traffic congestion is a major problem in our country, which affects modern city’s daily life routine and environments. Due to population growth, the size of cities expands, automatically the number of vehicles increases in the major scale on roads. So, traffic monitoring and controlling is the biggest challenge on traffic management authorities. In many urban areas, most of the traffic signal lights are based on a fixed cycle protocol, which is a reason for the inefficient controlling. Thus, there is an immoderate need to enhance and automate these traffic systems. We design and develop a system for real-time traffic monitoring using the Internet of Things (IoT) platform and sensing technology. Proposed work identifies the traffic conditions based on vehicle numbers on road and makes decisions for a control system with sharing their data synchronously with each other. In addition, the proposed system can send traffic signal data to other signals and people can retrieve traffic situation anywhere. This paper provides an insight into how these technologies can be applied and how it helps to overcome traffic congestion to reduce travel time.